Coupling mechanism of seepage and coal and rock mass destruction during coal and gas outburst - Shiling ZHANG; Junfei CUI; Shudong HE (Meitan kexue jishu)
In response to the unclear mechanism of coal and gas outburst, the mechanical action mechanism of gas seepage on coal body damage and coal and gas outburst in working face was studied.The concept of gas permeability as a cohesive force is introduced from the perspectives of coal seepage test and soil mechanics. The mechanical form of gas pressure gradient acting on coal is clarified. Based on elasticity and plasticity mechanics, the limit equilibrium equation of coal body in working face under the action of gas pressure is constructed, and then the seepage flow is coupled with the coal body stress in the limit equilibrium area. The mechanical reasons for the generation of tensile stress and tensile failure of coal under the action of gas pressure are obtained. From the perspective of permeability effect, the failure characteristics of the spalling in the protruding cavity wall and the distribution law of the spalling body are explained, revealing the mechanical nature of gas pressure in outburst coal seam failure. The results show that the permeability force of gas bearing coal body generated by gas flow is equal to the gas pressure gradient. From the energy point of view, the seepage force reflects the gas pressure energy loss per unit length. Permeability and surrounding rock supporting pressure act together on the coal body of the working face，which becomes an important inducement to destroy the coal body. The gas flow before outburst produces extremely high permeability in the coal wall of the newly exposed working face. The seepage force does not act uniformly in the coal wall, but concentrated in the thin layer less than 0.1 m near the exposed face of the coal wall. This action feature of seepage force makes the stress in the mining direction of coal body sharply reduce or even become negative to form tensile stress, which leads to the tensile failure and instability of the thin layer and the formation of spall. Permeability and stress in coal body change significantly with time. When the coal wall is just exposed, the seepage force is more than 6 times that of the stable seepage, and the corresponding maximum tensile stress is more than 5 times that of the stable seepage. With the increase of the exposure time of the coal wall and the progress of seepage, the seepage force is continuously reduced, the tensile stress is also gradually reduced, and the layered fracture body is gradually thickened. In this process, the strength of coal seams shows a trade-off relationship with the tensile stress on the coal body. The lower the coal seam strength, the greater the tensile stress generated, the more the tensile damage of gas pressure is brought into full play, which is characterized by gas dominated outburst and typical spall failure.